Surgical anatomy of cricothyroid membrane with reference to airway surgeries in North Indian population: a cadaveric study’ - Anand, Viswanathan; Sharma, Harikesh; Sethi, Ashwani; Sahoo, Satyanjaya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Surgical cricothyroidotomy is used to rapidly gain entry into the subglottic airway by creating an opening in cricothyroid membrane. The size and position of cricothyroid membrane is variable depending on racial characteristics of the individual. Statistics regarding dimensions of cricothyroid membrane has been documented extensively in Caucasian race. This study aims to augment the meagre information available on the Indian population on this important part of upper airway. Methods: Morphometric cadaveric analysis done in tertiary health care centre. 39 adult human cadaveric larynges were obtained for this study. Using electronic Vernier caliper, different dimensions of cricothyroid membrane and depth of subglottis were noted down in predesigned proforma in standard office software. Data obtained was collated and compared with existing literature. Results: The average dimensions of cricothyroid space and cricothyroid membrane were uniformly larger in males compared to females. Mean middle width F: 10.92±1.57 mm, M: 13.84±2.54 mm; mean height F: 7.26±1.82 mm, M: 9.61±1.86 mm; mean thickness F: 2.89±0.22 mm, M: 4.53±0.92 mm and mean subglottic depth F: 17.24±2.09 mm, M: 21.94±2.93 mm. Conclusions: Inter specimen disparity was noted. As cricothyroid membrane is smaller in Indian population compared to Caucasian population, ET tubes size 3.0 to 5.0 in females and 4.0 to 6.0 in males are suggested for use for cricothyroidotomy. Oversized tubes are known to cause dysphonia, laryngeal damage and subglottic stenosis.